Current and Emerging Strategies in Osteoporosis Management - Ivanova, Stefka; Vasileva, Liliya (Current Pharmaceutical Design, 2017)
The abnormal loss of bone tissue is defined as osteoporosis. Increased risk of fractures, low bone mineral density (BMD) and loss of the structural and biomechanical properties of the bone tissue characterize this pathological condition. Physiologically bone undergoes a continuous remodeling process involving balance between the activity of osteoblast and osteoclast. Disruption in this balanced condition increases the risk of osteoporosis. Both sexes are affected, but with higher prevalence in women after menopause. This review aims to enlighten the established and emerging trends in prevention and treatment of bone loss. Herbal supplementation and physical exercises are suggested as addition to the well-established therapy in prevention and management of osteoporosis. Treatment strategies of osteoporosis include non- pharmacological treatment - diet rich of calcium and vitamin D, healthy lifestyle, proper exercise plan, and pharmacological therapy. Preventive and treatment strategies have to consider combination of non-pharmacological and pharmacological approaches for minimization of the fracture risk in osteoporosis.
Keywords: prevention